Penentuan Mutu Buah Pepaya California (Carica Papaya L.) Menggunakan Fuzzy Mamdani - Al Rivan, Muhammad Ezar; Suherman, Jessica (Faculty of Engineering, Universitas Tanjungpura, 2020)
Papaya (Carica papaya, L.) is a fruit that has good nutritional content for health so that it has a high selling value and is made a business commodity. One variety of papaya fruit that is currently favored by all people, namely the California papaya fruit. Determination of the quality of California papaya fruit can be measured by size, color, and defect. This study raises the topic of determining the quality of California papaya fruit using fuzzy-Mamdani with input variables in the form of major axis, minor axis, red, green, and defect variables along with the output in the form of the results of determining the quality of California papaya fruit. Based on testing that has been done using 108 fuzzy rules, the validity of the results obtained states that the level of accuracy of the research using defuzzification of the Centroid, Bisector and Means of Maximum methods by 75%, while the level of research accuracy using the defuzzification of Largest of Maximum and Smallest of Maximum methods by 70%